Longitudinal effects of role stressors on strain: a comparison between three competing analytical approaches - Idris, Mohd Kamel (Faculty of Economics and Management, Universiti Putra Malaysia, 2011)
Role stressors (role overload, role ambiguity and role conflict) were used to predict strain among samples from Malaysian public university academics. A longitudinal survey with a six-month time interval yielded 310 academics for time 1 and 194 academics for Time 2. The study successfully matched only 170 respondents at Time 1 with respondents at Time 2. The study used three analytical approaches to infer causal relationships: (a) relationships between variables at Time 1 and Time 2, (b) the effects of predictors at Time 1 on changes in criterion variables, and (c) effects of changes in predictor variable on changes in criterion variables. Based on approach 1, only role conflict was related to strain within a six-month lag time. Based on approach 3, role overload and role ambiguity were related to strain. The findings of the study highlight the contribution of sustained role overload and role ambiguity to strain among academics.